Failing to Master Divinity: How Institutional Type, Financial Debt, Community Acceptance, and Gender Affect Seminary Graduates' Career Choices - Ferguson, Todd W. (Review of religious research, 2015)
Seminaries, as both educational and religious organizations, have the goal of training religious leaders. In this article, I analyze the factors associated with the breakdown of this process, i.e. when a seminarian does not want to be in a religious career. I offer four reasons for this breakdown: institutional type, financial strain, community acceptance, and gender. Drawing on recent survey data of 3015 American and Canadian seminarians graduating with the Master of Divinity degree from 136 seminaries from the Association of Theological Schools, I interpret results from multilevel logistic regressions testing five hypotheses. I find that Master of Divinity graduates who attend a university-affiliated seminary are less likely to want to be in a religious career, while those who feel more accepted within the seminary community are more likely. Educational debt has no effect. Most importantly, gender has profound effects on the choice to enter a religious career.